Natural Buffering of Groundwater Contaminants Related to Development in Fractured Rock. Issue 4 (22nd October 2013) - Metcalf, Meredith J.; Robbins, Gary A.
Abstract In rural areas of New England groundwater from fractured crystalline and sedimentary bedrock is a critical water resource. Increasingly, studies have shown that development occurring in rural areas is resulting in the impairment of water quality in fractured rock aquifers. The objective of this study was to evaluate the spatial and temporal variations in groundwater quality associated with development and evaluate the extent to which common groundwater contaminants associated with rural development may be naturally buffered. The study entailed a compilation and synthesis of over 2500 reports on domestic water quality that spanned a 30 year period. Focus was placed on the spatial distribution and temporal variations in sodium, chloride, iron, manganese, nitrate, and nitrite. Results indicate that despite significant levels of development, the amount of contamination to the bedrock has been minimal. Of the constituents examined, only the chloride concentration exhibits a systematic increase over time, but the level of chloride remained relatively low. The flux of chloride to the bedrock from deicing appears minimal despite the significant amounts of road salt used in the study area. Sodium concentrations in the bedrock remained relatively constant and appear to be buffered by ion exchange with calcium as suggested by the increase in hardness with time. Iron and manganese were present at relatively low levels but did not show any systematic trends over time. Nitrate and nitrite concentrations were very low and found to be inversely correlated with manganese and iron concentrations. This suggests that the presence of iron and manganese contribute to denitrification. This study indicated that both geochemical and biogeochemical processes are active buffering mechanisms that help shield the bedrock from contaminants associated with development.